The application of chair homogeneity index: The advantages of DMLC over VMAT in the radiotherapy for esophageal cancer. Issue 1 (March 2022) - Xi, Dan; Jiao, Tongli; Mu, Jinming; Chen, Yuan; Gu, Wendong; Li, Qilin
Abstract: Dynamic multileaf-collimator (DMLC) and volumetric modulation arc therapy (VMAT) were compared carefully in radiotherapy for esophagus cancer (EC) with the help of a new plan quality index: chair homogeneity index (CHI). Thirty-five patients with EC who underwent RT were enrolled. The prescription for the planning tumor volume (PTV) was 54Gy/25f and for the boost volume was 60Gy/25f. Two plans were designed for each patient: DMLC and VMAT. The dose-volume constraints were the same for two kinds of plans of each patient. CHI was an index developed by us and described the dose heterogeneity in the PTV but excluding the Boost (P–B). Heterogeneity index (HI), conformity index (CI) and other plan qualities indexes were also collected. The mean CHIs of PTV and P–B were 1.70 and 1.79 in DMLC, significantly higher than 0.82 and 0.86 in VMAT, respectively. The mean HIs of PTV and PTV-Boost were 17.79% and 15.55% in DMLC, slightly higher than 19.33% and 16.83% in VMAT, respectively. From the data aforementioned, DMLC is superior to VMAT in the treatment for EC. The high values of CHI in plans with DMLC proposed that DMLC achieve a more ideal dose distribution inside a compound target than VMAT.